Dysfunction of the Default Mode Network in Drug-Naïve Parkinson’s Disease with Mild Cognitive Impairments: A Resting-State fMRI Study - Hou, Yanbing; Yang, Jing; Luo, Chunyan; Song, Wei; Ou, Ruwei; Liu, Wanglin; Gong, Qiyong; Shang, Huifang (Frontiers in Aging Neuroscience, 2016)
Objective: Cognitive impairments are common in Parkinson’s disease (PD) and can even occur in the early stages. The default mode network (DMN) is highly relevant for cognitive processes; however, it remains largely unknown if changes in the DMN connectivity are related to the cognitive decline in drug-naïve early-stage PD patients with a mild cognitive impairment (MCI). This study used resting-state functional MRI (fMRI) to explore the brain connectivity of the DMN in early-stage drug-naïve PD patients with MCI. Method: We recruited 32 early-stage drug-naïve PD patients and 22 matched healthy controls (HC). Among the PD patients, 14 were classified as having MCI (PD-MCI) and 18 were classified as having unimpaired cognition (PD-CU). The functional integration of the DMN was evaluated by a seed-based correlation approach. Results: The brain connectivity analysis revealed reduced functional connectivity (FC) in both PD subgroups compared with HC. The PD-MCI group showed a significant reduction in FC between the DMN and a set of regions, including the precentral gyrus, middle temporal gyrus, insula, anterior inferior parietal lobule and middle frontal gyrus. Compared to the PD-CU group, the PD-MCI group demonstrated a significantly decreased FC in the middle frontal and middle temporal gyri. Additionally, compared to HC, the PD-MCI group had a significantly decreased FC within the DMN, mainly in the FC between the hippocampal formation and inferior frontal gyrus, between the posterior cingulate cortex and posterior inferior parietal lobule, and between the anterior temporal lobe and inferior frontal gyrus. Compared to the PD-CU group, the only significantly decreased FC within the DMN in the PD-MCI group was between the anterior temporal lobe and inferior frontal gyrus. In all PD patients, the decreased FC between anterior temporal lobe and middle temporal gyrus was positively correlated with attention/working performance, and the reduced FC between the hippocampal formation and inferior frontal gyrus was also positively correlated with memory function. Conclusions: Our findings suggest that an altered DMN connectivity characterizes PD-MCI patients. These findings may be helpful for facilitating the further understanding of the potential mechanisms underlying MCI in PD. However, our results are preliminary, and further investigation is needed.